Intestinal function and transit associate with gut microbiota dysbiosis in cystic fibrosis - Marsh, Ryan; Gavillet, Helen; Hanson, Liam; Ng, Christabella; Mitchell-Whyte, Mandisa; Major, Giles; Smyth, Alan R; Rivett, Damian; van der Gast, Christopher (Journal of cystic fibrosis, 2022)
•Faecal microbiota significantly differs between pwCF and healthy controls.•Known SCFA producers contributed to microbiota dissimilarity between groups.•Pulmonary antibiotic treatment heavily impacted gut microbiota.•Intestinal physiology and transit impacted satellite microbiota composition. Most people with cystic fibrosis (pwCF) suffer from gastrointestinal symptoms and are at risk of gut complications. Gut microbiota dysbiosis is apparent within the CF population across all age groups, with evidence linking dysbiosis to intestinal inflammation and other markers of health. This pilot study aimed to investigate the potential relationships between the gut microbiota and gastrointestinal physiology, transit, and health. Faecal samples from 10 pwCF and matched controls were subject to 16S rRNA sequencing. Results were combined with clinical metadata and MRI metrics of gut function to investigate relationships. pwCF had significantly reduced microbiota diversity compared to controls. Microbiota compositions were significantly different, suggesting remodelling of core and rarer satellite taxa in CF. Dissimilarity between groups was driven by a variety of taxa, including Escherichia coli, Bacteroides spp., Clostridium spp., and Faecalibacterium prausnitzii. The core taxa were explained primarily by CF disease, whilst the satellite taxa were associated with pulmonary antibiotic usage, CF disease, and gut function metrics. Species-specific ordination biplots revealed relationships between taxa and the clinical or MRI-based variables observed. Alterations in gut function and transit resultant of CF disease are associated with the gut microbiota composition, notably the satellite taxa. Delayed transit in the small intestine might allow for the expansion of satellite taxa resulting in potential downstream consequences for core community function in the colon.